Influence of Ethnoeducational Space of Educational Establishment to the Training of the Future Music Teacher - Liudmyla Vroda (Pedagogical Discourse, 2015)
This article addresses some aspects of creation of ethnic educational environment of the educational establishment in the process of preparation of the future teachers of music. Educative environment of general educational institution is studied as natural and socio-cultural environment of the personality, the goals and purpose of which are in forming of national conscious patriot of the motherland, able to teach the students best human features. The opportunities of ethnic educational environment of educational establishments to exploit widely the potential of ethno pedagogy not only in compulsory educational programs, but also in extracurricular activities, special courses have been grounded. The attention is accentuated on the study of ethnology and professionally directed subjects and inclusion of students into the created ethnic environment through pedagogical, and artistic-creative activities.